Peningkatan Kualitas Pembelajaran Mahasiswa Dengan melibatkan Masyarakat Dalam Wisata Pendidikan Pada Kuliah Kerja Nyata di Makassar - Oki, Alber; Almutiah, Bahjatul Khasna; Mutmainnah, Mahirah; Khaqiqoh, Khannnifatul; Nurhidayati, Alfi (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2024)
This article discusses the experience of educational tourism in the community service program (KKN) in Makassar. The purpose of this service is to improve student learning and also community involvement. This service method is a field service method. Based on the results of the service, educational tourism is a form of travel that combines tourism activities with educational aspects. This journal explores the positive impact of KKN in enhancing student skills as well as its contribution to local community empowerment.